Information Disclosure And Waqif Commitment: The Role Of Trust As Mediator And Communication As Moderator - Jalil, Mohamad I’sa Abd (2018)
The role of cash Waqf as a solution to the problem of idle Waqf land is no longer questionable. However, after 34 years of the implementation of cash Waqf in Malaysia, the struggle of the lack of capital and limited financial resources to promote idle Waqf assets remains a vital issue. One way to maintain and increase cash Waqf collection is by multiplying the committed Waqif. Therefore, this study attempts to unravel the issue by exploring the relationship between the attitude of Waqif commitment to donate more, the degree of trust among Waqif, information disclosure from Waqf institution and communication. Apart from regression test, this study also examines the role of trust as mediator and communication as moderator.